2020
DOI: 10.3390/bioengineering7020042
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Vivo Stimulation of Adipose Stem Cells by Growth Factors and Fibrin-Hydrogel Assisted Delivery Strategies for Treating Nerve Gap-Injuries

Abstract: Peripheral nerve injuries often result in lifelong disabilities despite advanced surgical interventions, indicating the urgent clinical need for effective therapies. In order to improve the potency of adipose-derived stem cells (ASC) for nerve regeneration, the present study focused primarily on ex-vivo stimulation of ASC by using growth factors, i.e., nerve growth factor (NGF) or vascular endothelial growth factor (VEGF) and secondly on fibrin-hydrogel nerve conduits (FNC) assisted ASC delivery strategies, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Nerve tissue engineering holds promise for developing a viable new strategy subjective to the availability of effective neurotrophic cell sources [ 68 ]. MSC derived from variety of tissues have been widely known to possess multilineage capacity and multifunctional potency [ 28 , 37 , 51 , 68 ]. The ability of these cells to support the trophic needs of the neuronal cells for survival, development, and plasticity can be defined as “neurotrophic capacity” within the context of functional multipotency of the stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nerve tissue engineering holds promise for developing a viable new strategy subjective to the availability of effective neurotrophic cell sources [ 68 ]. MSC derived from variety of tissues have been widely known to possess multilineage capacity and multifunctional potency [ 28 , 37 , 51 , 68 ]. The ability of these cells to support the trophic needs of the neuronal cells for survival, development, and plasticity can be defined as “neurotrophic capacity” within the context of functional multipotency of the stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cell with improved trophic capacity for addressing the complex needs of severed nerves would circumvent the side effects associated with application of large number of exogenous factors [ 29 ]. ASC and SCLC were shown to support nerve regeneration by releasing a variety of biological factors with mitotic and neuritogenic activity, although neurotrophic capacity of ASC is still inferior to SC [ 51 ]. Growth factors and related receptors play key role in the SC lineage and their autocrine survival loop [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the increasing demand for large-scale cell manufacturing protocols, there is a critical need to establish potency assays for stem cell therapy products and their derivatives. Katharina M. Prautsch and colleagues [ 7 ] developed a strategy to improve the potency of ASC for nerve regeneration through ex vivo stimulation of ASC with nerve growth factor (NGF). The authors found that the secretome from NGF-stimulated ASC promoted significant axonal outgrowth in an in vitro setting.…”
mentioning
confidence: 99%